PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA KEHUTANAN (Studi Putusan Kasasi Mahkamah Agung RI Nomor 2642 K/Pid/2006) - Mazmur Septian Rumapea; Alvi Syahrin; Muhammad Hamdan; Edy Ikhsan (Universitas Sumatera Utara, 2016)
ABSTRACT The corporation case which occurs in North Sumatera is a forestry criminal act committed by Darianus Lungguk Sitorus, the owner of PT Torganda and PT Torus Ganda. He did forestry criminal act in the area of Hutan Padang Lawas through his corporation. As the perpetrator who did the criminal act in this case, he was imprisoned by the Ruling of the Supreme Court No 2642 K/Pid/2006 for 8 (eight) year imprisonment plus incurred a fine of Rp. 5,000,000,000 (five billion rupiahs) plus confiscation of 47,000 (forty seven thousand) hectares of oil palm plantation, located in the area of Padang Lawas by the Department of Forestry.The problems of the research were the development of corporation responsibility for forestry criminal act in Indonesia and whether judge’s legal consideration on corporation criminal responsibility in the Cassation Ruling of the Supreme Court No 2642 K/Pid/2006 had met the theory of criminal responsibility. The research used judicial prescriptive method with legal provision, case, and comparative approaches, using primary, secondary, and tertiary legal materials which were analyzed interpretatively. The result of the research showed that corporation criminal responsibility in forestry criminal act in Indonesia is developing in ius constitutum which indicated by the development of the development of legal subject and corporation criminal responsibility. Law No. 41/1999 on Forestry which has gone through the development of corporation criminal responsibility in Law No. 18/2013 on Prevention from and Eradication of Forest Damage, and Cassation Ruling of the Supreme Court No. 2642 K/Pid/2006 has directly used the theory of corporation criminal responsibility. As a directing mind, Darianus Lungguk Sitorus had a corporation inner-self in ordering to commit (doen plegen) forestry criminal act. Keywords: Criminal Responsibility, Corporation, Forestry Criminal Act